Advanced Composite Biomaterials - Voicu, Stefan Ioan; Miculescu, Marian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Biomaterials is currently one of the most important fields of study. This is because of the high degree of interdisciplinarity and the many practical solutions it provides in relation to medicine, biology, chemistry, and physics. This Special Issue provides readers with research from the domain of composite biomaterials in different applications, from controlled drug release systems to tissue engineering.